Brassica napus L. Napobrassica Group NGB 16256 ... - GLIS Of The ITPGRFA (Nordgen, 2024)
Plant Genetic Resource. Taxonomy: Brassica napus L. Napobrassica Group Common name(s): BrassicaComplex, Brassica complex Other names: Vestmannaeyjar Conserved by: Nordgen (NORDGEN), Sweden Local sample unique identifier: NGB 16256 Method of creation: Acquisition Date: 2004-10-25 Historical: Yes Biological status: Traditional cultivar/landrace MLS status: Included ...